THE EFFECT OF USING RING HEAVENER ON CATCH RESULTS IN GILLS NETWORK CAP IN KELURAHAN NIPAH PANJANG 1 TANJUNG JABUNG EAST JAMBI PROVINCE DISTRICT - Sunjaya, Legi; Nofrizal, Nofrizal; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted on 15-31 October 2019 in Nipah Panjang 1 Kelurahan, Tanjung Jabung Timur Regency, Jambi Province. The purpose of this study is to determine the effect of the use of ring shaped ballast with oval lead ballast on the gill surface fishing gear, so that it can find out which ballast is good to use by looking at the number of catches. The method used in this study is an experimental method that is by using 2 types of gill nets with ballast in the form of a ring and oval tin ballast by using 2 fishing vessels in Nipah Panjang Village 1. From the results of the research that the fishing gill net with ballast ring and oval tin ballast there are differences in the construction components. Where the construction of gillnet gillnet fishing gear construction does not use a lower ris rope, because the ballast ring is fastened directly to the lower net. Whereas in the construction of oval tin gill net fishing gear construction uses a lower ris rope. For the number of catches according to weight (kg) during capture (7 days) the most is on gill net fishing gear with oval tin weights ranging from 91.6 kg / day with an average of 13.09 kg / day. While the number of catches on gillnet fishing gear that uses a ballast ring ranges from 78.6 kg / day with an average of 11.23 kg / day. Therefore, there is no difference in catches in the ballast gill net and oval tin fishing gear.Keywords: gill net fishing gear, ballast ring, construction, troop fish